20-Year Outcomes of Anterior Cruciate Ligament Reconstruction With Hamstring Tendon Autograft: The Catastrophic Effect of Age and Posterior Tibial Slope. Issue 3 (March 2018) - Salmon, Lucy J.; Heath, Emma; Akrawi, Hawar; Roe, Justin P.; Linklater, James; Pinczewski, Leo A.
Background: No well-controlled studies have compared the long-term outcome of anterior cruciate ligament (ACL) reconstruction with hamstring tendon autograft between adolescents and adults. Increased posterior tibial slopes (PTSs) have been reported in the ACL-injured versus controls, but the effect of PTS on the outcome after reconstruction is relatively unexplored. Purpose: To compare the prospective longitudinal outcome of "isolated" ACL ruptures treated with anatomic endoscopic ACL reconstruction using hamstring tendon autograft over 20 years in adolescent and adult cohorts and to examine factors for repeat ACL injury. Study Design: Case-control study; Level of evidence, 3. Methods: A single-surgeon series of 200 consecutive patients undergoing isolated primary ACL reconstruction with hamstring tendon autograft were prospectively studied. Subjects were assessed preoperatively and at 2, 7, 15, and 20 years postoperatively. Outcomes included International Knee Documentation Committee (IKDC) Knee Evaluation, IKDC subjective scores, KT-1000 instrumented laxity testing, and radiological evaluation of degenerative change and medial tibial slope. Twenty-year outcomes were compared between those who underwent surgery at the age of 18 years or younger (adolescent group, n = 39) and those who underwent surgery when older than 18 years (adult group, n = 161). Results: At 20 years, 179 of 200 subjects were reviewed (89.5%). ACL graft rupture occurred in 37 subjects and contralateral ACL injury in 22 subjects. Of those with intact ACL grafts at 20 years, outcomes were not statistically different between adolescents and adults for the variables of IKDC subjective score ( P = .29), return to preinjury activity level ( P = .84), current activity level ( P = .69), or degree of radiological degenerative change at 20 years ( P = .51). The adolescent group had a higher proportion of grade 1 ligamentous laxity testing compared with the adult group ( P = .003). Overall, ACL graft survival at 20 years was 86% for adults and 61% for adolescents (hazard ration, 3.3; P = .001). The hazard for ACL graft rupture was increased by 4.8 in adolescent males and 2.5 in adolescent females compared with adults. At 20 years, the ACL survival for adolescents with a PTS of ≥12° was 22%. The hazard for ACL graft rupture was increased by 11 in adolescents with a PTS of ≥12° ( P = .001) compared with adults with a PTS <12°. Conclusion: Repeat ACL injury after isolated ACL reconstruction is common, occurring in 1 in 3 over 20 years. In the absence of further injury, isolated ACL reconstruction using this technique was associated with good long-term outcomes with respect to patient-reported outcomes and return to sports, regardless of age. However, mild ligament laxity and ACL graft rupture after ACL reconstruction are significantly more common in adolescents, especially adolescent males, compared with adults. PTS of 12° or more is the strongest predictor of repeat ACL injury, and its negative effect is most pronounced in adolescents.